A Contribution Evaluation and Reward Framework Based on Shapley Value and Smart Contract - Chen, Shengdong; Guo, Zhanwei; Liu, Tianyou; Zhang, Tianwen (Innovative Applications of AI, 2024)
Currently, due to the advantages of Shapley values in explaining model decisions, incentive mechanisms based on Shapley value contribution assessment have become a major research focus. This approach ensures the effectiveness and fairness of contribution assessment algorithms. However, there is a problem regarding the reliability of the computational results. Additionally, traditional Shapley value-based contribution processes face an issue where computational complexity increases exponentially with the number of participants. To address these issues, this paper proposes a contribution assessment and reward framework based on Shapley values and smart contract technology using alliance blockchain. This framework overcomes the reliance on third-party institutions that is characteristic of traditional incentive mechanisms, leveraging the decentralized nature of blockchain to eliminate trust issues associated with a single centralized entity. Furthermore, the traceability of blockchain ensures the transparency and traceability of the contribution assessment and reward distribution processes.